Religious survival of Hindus in the context of Islamic Malaysian environment - Jaffary Awang,; Ros Izanie Ismail,; Indriaty Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Hindu community is a minority group in Malaysia, living together with the majority of Muslim Malays. Following their migration to Malaysia during British colonisation, the Hindus have to endure various challenges. This study discusses the survival of Hindus in dealing with their religious concerns in the Malaysian Islamic environment. The issue that was identified and triggered critical concern among the scholars is the Islamisation agenda. A qualitative approach is employed to fulfil the objective of this study, which entails analysing works of literature. This study finds that the Islamization agenda discussed to be a major concern in the survival of the Hindu community is its apparent application from the government’s Islamisation of policies, including the land allocation for temples and shrines and religious conversion. The findings also reveal that, despite the intimidation perceived by the Hindus on Islamisation, it has played a vital role in reforming their religion.